Efektivitas Integrasi Model Think Pair Share dan E-Modul dalam Pembelajaran Matematika: Systematic Literature Review - Rahmi Novalina; Yufitri Yanto; Drajat Friansah (Proceeding of Silampari Conference of Life Science and Technology, 2026)
This study aims to examine the implementation of the Think Pair Share (TPS) cooperative learning model assisted by E-Modules in mathematics learning through the Systematic Literature Review (SLR) method. Articles were collected using the Publish or Perish application with the Google Scholar database within the period of 2021–2026. The initial search identified 82 articles, which were subsequently screened based on inclusion and exclusion criteria, resulting in 21 eligible articles for analysis. The findings indicate that the implementation of the TPS model has a positive impact on mathematics learning, including improvements in learning outcomes, conceptual understanding, mathematical communication, learning motivation, problem-solving skills, and students' mathematical reasoning abilities. In addition, the use of E-Modules contributes to enhancing problem-solving skills, mathematical understanding, numeracy skills, learning interest, critical thinking, and students' learning independence. The review also reveals that E-Modules can be integrated with various learning models and approaches, such as Problem-Based Learning, Problem Solving, Contextual Teaching and Learning, inquiry-based learning, and TPS. Therefore, the implementation of the TPS learning model supported by E-Modules can serve as an alternative approach to mathematics instruction that is more interactive, innovative, and effective in supporting students' learning processes.